Workbook - Pratico, Gary Davis (U.S.A, 2019)
This updated workbook is designed with the student in mind and intended for use with the standard-setting Basics of Biblical Hebrew Grammar textbook, now in its third edition. In addition to corresponding to the revisions and updates in Basics of Biblical Hebrew Grammar, this workbook includes significant changes to the interior presentation
Keywords: Hebrew language - Grammar